2020
DOI: 10.1002/cam4.3228
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sorafenib starting dose and dose intensity on survival in patients with hepatocellular carcinoma: Results from a Canadian Multicenter Database

Abstract: Background Sorafenib has been shown to improve survival in patients with advanced hepatocellular carcinoma (HCC), however, full dose can be difficult to tolerate. The aim of this study was to determine whether sorafenib starting dose and mean dose intensity affect survival. Methods Patients treated with sorafenib for HCC from January 2008 to July 2016 in several Canadian provinces were included and retrospectively analyzed. The primary end point was overall survival (OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…However, in clinical practice, a considerable proportion of patients with advanced HCC does not fulfill the inclusion criteria of a clinical trial, and in the real-world setting, it is not uncommon that lenvatinib treatment is initiated at a lower than recommended dose. Similar to the observations published for sorafenib, our data suggest that a reduced lenvatinib dosage may be a safe and a reasonable strategy for some patients with HCC [29].…”
Section: Discussionsupporting
confidence: 88%
“…However, in clinical practice, a considerable proportion of patients with advanced HCC does not fulfill the inclusion criteria of a clinical trial, and in the real-world setting, it is not uncommon that lenvatinib treatment is initiated at a lower than recommended dose. Similar to the observations published for sorafenib, our data suggest that a reduced lenvatinib dosage may be a safe and a reasonable strategy for some patients with HCC [29].…”
Section: Discussionsupporting
confidence: 88%
“…[15][16][17] Moreover, some studies on dose reduction initiation in multitargeted therapy for HCC have been reported for SOR treatment, with no difference in outcome and better safety in dose reduction initiation cases. [18][19][20] Optimizing the dosage according to the therapeutic situation is critical to maximize the effect of CAB treatment, and is considered beneficial as this study suggests the efficacy and safety of using a reduced dosage.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study found that small dose reductions in sorafenib were associated with longer adherence, higher cumulative dosage, and better overall survival compared with patients who maintained the standard dosage (21). Similar work was also shown by the HCC Cancer Health Outcomes Research Database (CHORD) consortium in Canada, who showed that neither starting dose (full 800mg/day versus reduced <800mg/ day) dose of sorafenib nor dose intensity compromise survival (22). Taken together, these results have important implications for the administration of first-line therapy for advanced HCC patients.…”
Section: Discussionmentioning
confidence: 57%